Influencia de fermentadores y tiempo de fermentación sobre la calidad del cacao de ascendencia nacional, en tres localidades de la provincia de Manabí. - Rivera Fernández, Rubén Darío (2009)
The present investigation was carried out among March and September of the 2008, in three localities of the province of Manabi. Its objective went to determine the influence of the type and of the time of fermentation in the quality of the National cocoa of ancestry and to transfer the results to them involved in the activity cacao;tera. It was studied four fermentadores: bag of jute, pile (upon wood), box of wood and have plastic with a capacity to store 60kg of cocoa in saliva, in times that went since two to five days of fermentacion; besides a witness was evaluated, that consisted of not fermenting. The complete design of blocks to the chance in arrangement was utilized factorial with additive (AxB+1) and three you retort (localities). The combination of the factors gave a total of 17 processing to which was carried out them volteos daily during the fermentation. It finished the fermentation 2kg of samples of each processing for the respective analysis was taken and subsequently was carried to spread them to dry it to a rank among 7 and 8% of humidity. It was analyzed statistically the physical variables: percentage of grains fermented, violet percentage of grains and percentage of grains pizarrosos evaluated by means of the test of cut; were also interpreted the chemical variables polifenoles, acidity volatil, caffeine and teobromina analyzed in the laboratories of Nutricion and Quality of the Holy Experimental Station Catalina of the IN IAP. The results show that so much the time as the type of fermented influence in the majority of the variables studied and by ende in the final quality of the cocoa. Thus same, difference among localities in the variable was found caffeine and teobromina. The results presented as better alternative, to ferment five days utilizing like fermented boxes of wood. However, taking into account the estimation of costs would be able to diminish the time to so alone three or four days at most. The trasferencia of results was carried out by means of chats groupies directed 250 persons among producers and farm students of schools and universities involved in the activity cacaotera, in five cantons of the province of Manabi.